Impact of High and Medium Velocity Resistance Training on Speed Endurance among Youth Boys - Suresh, R (International Journal of Pharmaceutical & Biological Archive, 2014)
Impact of High and Medium Velocity Resistance Training on Speed Endurance among Youth Boys